The Validity of Interactive E-Book on Human Heredity Material to Improve Critical Thinking Skills of 12th Grade High School Students - Reftiyana, Diva; Susantini, Endang (Berkala Ilmiah Pendidikan Biologi (BioEdu), 2025)
One of the learning outcomes in the independent curriculum is to be able to establish students' critical thinking skills. The ability to think critically is still low from year to year because students lack opportunities to practice critical thinking skills. Teaching materials that can be used to improve students' critical thinking skills are interactive e-books. The purpose of this research is to describe the validity of interactive e-books on human heredity subject to improve the critical thinking skills of 12th grade high school students. This type of research is development research with the ADDIE model. At the development stage, the validity of the interactive e-book was measured from the results of validation by three validators. At the implementation stage, the research was conducted on 31 students of class XII at SMAN 1 Sugihwaras, Bojonegoro. Data collection techniques were carried out by validation methods and analyzed descriptively quantitatively. The validation results were declared highly valid with an average percentage of content eligibility of 90.5%, presentation eligibility of 92.5%, and linguistic eligibility of 100%. Based on the three eligibility criteria, the overall average percentage of 90% was obtained, indicating a highly valid category. The interactive e-book has four main features accompanied by several tasks and contains four critical thinking indicators (interpretation, analysis, explanation, and evaluation) that must be answered by students, so that this interactive e-book on human heredity material can improve students' critical thinking skills. The results of the study recommend that every school and biology teacher use interactive e-books as teaching materials to deliver heredity material as well as improve critical thinking skills.